Enhancing Writing Skills through Intercultural-Based Metacognitive Strategies - Ilham (IKIP Siliwangi, 2025)
This systematic literature review explores the impact of interculturally-based metacognitive strategies in improving academic writing in higher education. The study examines the various components of these strategies, including declarative, procedural, and conditional knowledge, and their role in improving writing proficiency, especially for ESL and multilingual learners. Key strategies such as planning, monitoring, and evaluating were found to significantly influence students' writing outcomes by fostering metacognitive awareness and promoting critical thinking. Moreover, the integration of cultural awareness with metacognitive practices enriches students' ability to adapt their writing style to diverse academic contexts and audiences. This research highlights the role of immersive learning environments and learning strategies in strengthening these skills. Despite the benefits, challenges related to the gap between theory and practice and cultural nuances in strategy implementation remain. The review concludes by emphasizing the need for further research to address these challenges and optimize the integration of cross-culturally based metacognitive strategies in academic writing curricula.